KEPEMIMPINAN PENDIDIKAN ANTI KORUPSI PERSPEKTIF PENDIDIKAN ISLAM - Abdan Rahim (STAI AL FALAH Banjarbaru, 2019)
Every organization and all organizations of any kind must have and need a leader and the highest leader (top leader) or the highest manager (top manager) who must carry out leadership activities (leadership action) or management (management) for the whole organization as a whole. The leader is the first person, like a ship captain who must direct the course of the ship, in a container called the organization. Anti-corruption education can be interpreted as an effort to minimize and eradicate corruption through education. Education is chosen as one of the alternatives to eradicate corruption because education itself has two essential functions, namely growing creativity and instilling and socializing noble values. Islam as a religion and a system of values plays an important role in providing enlightenment, moral awareness, mental improvement, and moral improvement by utilizing existing potential. Therefore, existing Islamic leaders must be the main role models to move towards moral revolution through the enlightenment of religious thought which liberates human behaviors with a mentality of corruption. Keywords: Leadership, Anti-Corruption Education, Islamic Education Perspective